Analisis Tingkat Kepuasan Pengunjung Wisata Kolam Pemancingan Habibi Ikhsan di Kelurahan Loa Bakung Kota Samarinda - Bayu Pratama; Erwiantono; Gusti Haqiqiansyah (2339-1324, 2023)
Fishing tourism is one of the attractions in the fisheries sector that has great potential, especially in Samarinda. Success in managing a fishing business needs a careful attention to the services provided. This study aims to determine the level of visitors' satisfaction at Kolam Pemancingan Habibi Ikhsan. This study utilizes accidental sampling method. The analysis of the data utilizes the analysis method of Community Satisfaction Index (CSI) and Importance Performance Analysis (IPA). According to the results of the analysis, the Community Satisfaction Index (CSI) is at 86.95, which means that it is within the category of good service quality. In addition, Importance Performance Analysis (IPA) shows that the satisfaction indicators that should be considered and become the main priority for improvements at Kolam Pemancingan Habibi Ikhsan are indicators that are in the quadrant A